Effects of school-based physical activity on academic achievement in children and adolescents: a systematic review and meta-analysis - He, Hongxue; Yang, Yahui; Sun, Jiaojiao; Wang, Fang; Zhang, Wei; Zhu, Fengshu (Frontiers in Public Health, 2025)
ObjectiveThis study explores how school-based physical activity affects the academic achievement of children and adolescents and examines whether factors like activity type or duration influence results.MethodWe registered the review in PROSPERO (CRD42024623670). We searched PubMed, Web of Science, Cochrane Library and Embase databases for peer-reviewed English-language randomized or quasi-experimental studies published through 8 December 2024. Reference lists and gray literature were reviewed. The Cochrane Risk of Bias Tool assessed study quality, with findings analyzed through subgroup and sensitivity analysis. Review Manager 5.4 calculated the standardized mean difference (SMD) and 95% confidence interval (CI) using a random-effects model.ResultsSeventeen studies met inclusion criteria. Meta-analysis indicated physical activity programs significantly improved academic achievement, especially in mathematics (SMD = 0.11, 95% CI: 0.04–0.18, p = 0.001; I2 = 55%) and overall academic achievement (SMD = 0.22, 95% CI: 0.01–0.44, p = 0.040; I2 = 74%). Subgroup analysis revealed moderate-intensity activity positively correlated with mathematics (SMD = 0.08, 95% CI: 0.01–0.15, p = 0.040; I2 = 37%) and overall academic achievement (SMD = 0.36, 95% CI: 0.14–0.57, p = 0.001; I2 = 70%) results. High-intensity activity showed a positive effect on mathematics (SMD = 0.41, 95% CI: 0.14–0.68, p = 0.003; I2 = 6%). Short-duration (<24 weeks) interventions positively impacted reading comprehension (SMD = 0.24, 95% CI: 0.03–0.46, p = 0.030; I2 = 69%), while longer interventions (≥24 weeks) improved mathematics (SMD = 0.13, 95% CI: 0.03–0.23, p = 0.010; I2 = 66%) and overall academic achievement (SMD = 0.47, 95% CI: 0.25–0.68, p < 0.001; I2 = 14%). Despite these significant findings, substantial heterogeneity was observed in several analyses, indicating that the results should be interpreted with caution.ConclusionSchool-based physical activity positively impacts academic achievement, particularly in mathematics and overall performance. Longer, moderate-intensity interventions are most effective, offering insights for future educational program development.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024623670, CRD42024623670.